Ready for Fall? Near-Term Effects of Voluntary Summer Learning Programs on Low-Income Students' Learning Opportunities and Outcomes - McCombs, Jennifer Sloan; Pane, John F.; Augustine, Catherine H.; Schwartz, Heather L.; Martorell, Paco (RAND Corporation, 2023)
The Wallace Foundation’s National Summer Learning Study, conducted by RAND and launched in 2011, offers the first assessment of district-run voluntary summer programs over the short and long run. This report, the second of five that will result from the study, looks at how summer programs affected student performance on math, reading, and social and emotional assessments in fall 2013.